What Design and Material Factors Impact the Wear and Corrosion Performance in Total Elbow Arthroplasties? - Figgie, Mark P. (Clin Orthop Relat Res, 2014)
BACKGROUND: The survivorship of total elbow arthroplasties is lower than surgeons and patients would like it to be, especially in patients with posttraumatic arthritis of the elbow. To improve durability, it is important to understand the failure modes of existing implants. Total elbow arthroplasties were designed primarily for low-demand rheumatoid patients. As surgical indications have extended to more active patient populations, the mechanical performance of current designs must meet an increased mechanical burden. Evaluating the degree to which they do this will guide conclusions about which contemporary devices might still meet the need and, as importantly, what design and material changes might be needed to improve performance. WHERE ARE WE NOW? The reasons for failures of total elbow arthroplasties include infection, loosening, polyethylene wear, locking mechanism failure, periprosthetic fracture, implant fracture, and instability. Implant design factors that have influenced wear include implant constraint, material, coatings, and metal backing. Surgical factors associated with increased wear and subsequent total elbow arthroplasty failure include soft tissue balancing and restoration of alignment and implant positioning. WHERE DO WE NEED TO GO? A clear need exists for improving the performance of total elbow arthroplasty. Many of the failures that have limited the survivorship of elbow arthroplasties thus far are mechanical in nature with wear-related problems a dominating influence. Much of what we know about the results of total elbow arthroplasty is from small studies frequently involving the designer of the implant. The establishment of total elbow arthroplasty registries coupled with the increasing regulatory burden of postmarket surveillance would lead to a better understanding of the complications and survivorship of elbow arthroplasties. Another primary goal must be to achieve a better understanding of the biomechanics of the normal elbow and how the mechanics are altered after the insertion of elbow arthroplasty components. HOW DO WE GET THERE? Improving the performance and survivorship of total elbow arthroplasty will require the integration of clinical and implant performance data gained through the establishment of registries with a concerted basic science effort to better understand the functional loads across the joint and to incorporate these loads into experimental and computational models to allow assessment of design and material changes intended to improve durability.